IMPORTANT STAGES OF COMPOSING IN FINE ARTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The student will learn the theoretical knowledge required to study carefully in creating a finished work step by step in the field of art and composition in the direction of majestic painting and form the skills to apply it in the creative process. Further strengthening is envisaged.